Antimicrobial susceptibility testing of Dermabacter hominis - Tim Kintzinger; Dennis Knaack; Sören Schubert; Uwe Groß; Robin Köck; Frieder Schaumburg (Microbiology Spectrum)
ABSTRACT Dermabacter hominis, a short gram-positive rod, is a part of the human skin flora, but can also cause infections (e.g., skin and soft tissue infections, bone and joint infections, abscesses, peritoneal dialysis-associated peritonitis, and bacteremia). Only limited data are available for antimicrobial resistance rates. Although CLSI does include coryneform genera in Corynebacterium spp. clinical breakpoints, they point out that only limited data are available on resistance rates. The aim of this study was to assess the minimal inhibitory concentration (MIC) of clinical isolates of D. hominis and to deduce breakpoints for disk diffusion. D. hominis (n = 30) from five laboratories in Germany were tested by broth microdilution and disk diffusion method. MICs were interpreted according to current clinical breakpoints for Corynebacterium spp. or pharmacokinetic–pharmacodynamic breakpoints (EUCAST). To deduce breakpoints for disk diffusion, MICs were correlated with inhibition zone diameters. All isolates were susceptible to vancomycin, rifampicin, and linezolid (100%, n = 30/30). Lower susceptibility rates were found for ampicillin (83%, n = 25/30) followed by ceftriaxone (37%, n = 11/30) and clindamycin (27%, n = 8/30). All isolates were resistant to benzylpenicillin and daptomycin. Good correlations between disk diffusion and MIC (suggested breakpoints for susceptibility in brackets) were found for ampicillin (S ≥ 10 mm), ceftriaxone (S ≥ 24 mm), clindamycin (S ≥ 19 mm), levofloxacin (I ≥ 24 mm), linezolid (S ≥ 29 mm), rifampicin (S ≥ 38 mm), and vancomycin (S ≥ 21 mm). Due to limited variances in both MIC values and inhibition zone diameters, no disk diffusion breakpoint could be deduced for gentamicin and benzylpenicillin in our dataset. D. hominis has favorable susceptibility rates for vancomycin, rifampicin, and linezolid and shows correlations between MIC and disk diffusion diameter for selected antimicrobial agents. Thus, the development of clinical breakpoints for disk diffusion appears feasible.IMPORTANCEDermabacter hominis can cause infections in humans (e.g., skin and soft tissue infections, bone and joint infections, abscesses, peritoneal dialysis-associated peritonitis, and bacteremia). Currently, only limited data are available regarding the resistance rates of this specific pathogen. Data for the easy accessible disk diffusion method are missing. We were able to provide additional data on resistance rates of clinical D. hominis isolates to common antimicrobial agents and correlate these with disk diffusion diameters to derive breakpoints to further improve the antimicrobial susceptibility testing for this specific pathogen. In addition to that, we created a current overview of resistance rates from the existing literature. Our data provide deeper insight into resistance rates and antimicrobial susceptibility testing of this specific pathogen.